Impact of collection from indigenous lands on the municipal solid waste management system: A case study in the Amazon (Research, Society and Development, 2023)
In the Amazon, solid waste collection is generally restricted to urban areas, excluding indigenous lands and rural areas. The objective of this research was to analyse the impact of collecting waste generated from indigenous lands on the municipal solid waste (MSW) management system, through life cycle assessment (LCA). A case study in the Humaitá city, state of Amazonas, Brazil, was based on life cycle inventory data, obtained from literature and field surveys, such as the waste gravimetry. The LCA followed the model proposed by ISO 14040 and 14044 and estimated greenhouse gas (GHG) emissions for three MSW management scenarios. The first, called Base Scenario (SB), corresponded to that practiced in Humaitá: collection of MSW from the urban area, logistic, and disposal in landfill. The second scenario (S1) corresponded to SB and the collection of waste generated on indigenous lands in that municipality. The third scenario (S2) corresponded to S1, excluding organic waste, which would be destined for composting on indigenous lands. The base scenario totalled an emission of 1,539 t CO2eq.year-1. Collecting solid waste from indigenous lands would increase these GHG emissions by 5.2% (S1) and 0.9% (S2) in relation to SB. The decentralized management of organic waste through composting associated with the separation and storage of dry waste would reduce the burning of waste in indigenous areas, their environmental vulnerability and promote the inclusion of these peoples.